Web application for pharmacy information system - Lim, Jian Wei. (2012)
The advantages of having pharmacy information systems are to allow pharmacists, pharmacy technician and nurse-in-charge have ease of usage, to keep track and maintain the medication stock in an organized and efficient manner. This system will also allow them to review and manage patients’ medication history.